A convenient sequencing method for 5' protein-linked RNAs. - Nomoto, A (1979)
A convenient nucleotide sequencing method for 5' end protein-linked RNAs was developed. Genome of LSc, 2ab poliovirus, which has a protein (VPg) covalently linked to the 5' terminus, was labelled with 125I Bolton and Hunter reagent after proteinase K treatment. No sign of labelling of nucleotide moiety in the genome with the reagent was detected. A labelled oligo peptide-linked ribonuclease T1 fragment was obtained from the 5' end of the genome. Analysis of the complex by two dimensional gel electrophoresis after partial alkali digestion or by the nucleotide sequencing method of Donis-Keller et al. (1) revealed that LSc, 2ab strain genome had an identical 5' end structure to that of Mahoney strain genome, that is, VPg-pUpUpApApApApCpApGp. Our results have shown that this labelling method is useful for analysis of 5' end sequence of RNAs linked to protein at the 5' termini.